2008 9th IEEE/ACM International Conference on Grid Computing 2008
DOI: 10.1109/grid.2008.4662819
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the DAG eligible jobs maximization algorithm in a grid

Abstract: A significant influence of heterogeneity and uncertainty of grid environment on quality of DAG schedules results in a search for new approaches. One of them is Internetbased computing scheduling approach and PRIO algorithm for DAG scheduling. In this paper, we present results of a detailed evaluation of the PRIO algorithms in a heterogeneous environment in which schedulers may recognize performance of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…They consider only the DAG structure to improve application performance. While in the evaluation of Szepieniec et al [149] showed that the effectiveness is limited without considering task execution time.…”
Section: Robust Workflow Schedulingmentioning
confidence: 99%
“…They consider only the DAG structure to improve application performance. While in the evaluation of Szepieniec et al [149] showed that the effectiveness is limited without considering task execution time.…”
Section: Robust Workflow Schedulingmentioning
confidence: 99%
“…Simulation experiments carried out in [14] indicate that ICO significantly improves the execution time of a large class of DAGs over three simple, intuitively compelling scheduling heuristics. Malewicz et al [9] extended the ICO algorithm to a practical heuristic applied in the Condor Project [11], and the usefulness of its implementation was assessed in [12], [21].…”
Section: Related Workmentioning
confidence: 99%
“…Several algorithms have been proposed for different types of Grids. This includes incremental workflow partitioning and full graph scheduling strategies [7], scheduling with communication and processing variations [8], QoS workflow scheduling with deadline and budget constraints [9], scheduling data intensive workflows [10], opportunistic workflow scheduling [11], and level based task clustering of data intensive workflows on computational grids [12].…”
Section: Related Workmentioning
confidence: 99%